STRESS-PERSONALITY RELATIONSHIP DURING COVID-19 RESTRICTIONS: A REVIEW (International Journal of Management, Public Policy and Research, 2022)
The unique and uncertain nature of the COVID-19 pandemic had made life miserable for everyone, causing physical and mental health problems. Psychological stress and anxiety were among the most common psychological outcomes. Previous studies explored that stress appraisal and management significantly depend upon the personality of people. Among the big five personality traits,  neuroticism and agreeableness traits make individuals vulnerable and extraversion, conscientiousness, and openness make people tough and resilient to stress and depressive symptoms. This study is to explore whether this personality-stress relationship is still applicable during this global stress crisis. Results showed that the pre-pandemic knowledge can not be generalized in full, which means that stress management interventions should be personality specific.
Keywords: Stress, Personality traits, Psychological strain, COVID-19, anxiety